Design of Pop-Up Interactive Illustration Book on The Education of Healthy Living Patterns for Children Aged 7-8 Years Old - Romadhona, Mahimma; Aileena S.C.R.E.C (Nusantara Science and Technology Proceedings, 2020)
The long-term objective of this research is the creation of a generation of Indonesians with healthy lifestyle habits, in which children can maintain personal and environmental hygiene to avoid disease attacks. The world is currently experiencing a pandemic due to the Coronavirus (COVID-19) outbreak which attacks humans and can cause death. One of the efforts to prevent the transmission of COVID-19 can be done by adopting a clean and healthy lifestyle. Healthy living habits are mandatory, but in reality, the knowledge and understanding of some people are still low so that people do not live healthily. For this reason, this study aims to educate children about the importance of healthy living interestingly and creatively, namely through the design of an interactive Pop-Up illustrated book for children aged 7-8 years. The method used is a qualitative research method. The design method uses 4 concepts including message concepts, creative concepts, media concepts, and visual concepts. The research process includes primary data collection and secondary data, structured interviews with children's book experts and doctors, as well as field tests and semi-structured interviews with children aged 7-8, namely students in grades 1-2 of elementary school to explore responses and children's understanding of the contents of the book. The sampling technique used is Non-Random Sampling-Purposive Sampling. The final results and conclusions of the study were to produce an Interactive Pop-Up Illustration Book About Healthy Lifestyle Education for 7-8 Years Old Children.